Alcohol use disorder and cannabis use disorder symptomatology in adolescents is associated with dysfunction in neural processing of future events. (5th March 2020) - Aloi, Joseph; Blair, Karina S.; Meffert, Harma; White, Stuart F.; Hwang, Soonjo; Tyler, Patrick M.; Crum, Kathleen I.; Thornton, Laura C.; Mobley, Alita; Killanin, Abraham D.; Filbey, Francesca M.; Pope, Kayla; et al.
Abstract: Two of the most commonly used substances by adolescents in the United States are cannabis and alcohol. Cannabis use disorder (CUD) and alcohol use disorder (AUD) are associated with impairments in decision‐making processes. One mechanism for impaired decision‐making in these individuals is thought to be an inability to adequately represent future events during decision‐making. In the current study involving 112 adolescents, we used a comparative optimism task to examine the relationship between relative severity of CUD/AUD (as indexed by the CUD/AUD Identification Tests [CUDIT/AUDIT]) and atypical function within neural systems underlying affect‐based neural represenation future events. Greater CUDIT scores were negatively related to responses within subgenual anterior and posterior cingulate cortex when processing high‐intensity potential future positive and negative events. There was also a particularly marked negative relationship between CUD symptoms and blood oxygen level‐dependent (BOLD) responses within visual and premotor cortices to high‐intensity, negatively valenced potential future events. However, AUD symptom severity was not associated with dysfunction within these brain regions. These data indicate that relative risk/severity of CUD is associated with reduced responsiveness to future high‐intensity events. This may impair decision‐making where future significant consequences should guide response choice. Abstract : This fMRI study examined adolescents with varying levels of cannabis use disorder (CUD) and alcohol use disorder (AUD) symptoms. Adolescents with greater severity of CUD symptoms were found to show dysfunction within subgenual anterior cingulate cortex and posterior cingulate cortex when processing future events; however, greater severity of AUD symptoms were not associated with similar dysfunctions within these brain regions.